Pelatihan Komunikasi Publik & Komunikasi Psikologi pada Pemilihan Duta Pendidikan Kabupaten Banggai Sulawesi Tengah - Surianto; Yuliani Clara, Yesica (LPPM Politeknik Piksi Ganesha, 2024)
The ability to communicate in an organization will allow each member to form connections, influence decisions, and motivate change. Public communication training at the Banggai Regency Education Ambassador Selection event, Central Sulawesi was carried out to train inspiring young figures who are specifically dedicated to the field of education, so that they are able to communicate effectively, efficiently, and appropriately. The method of implementing Community Service activities is carried out by presenting material that is collaborated with interactive activities such as questions and answers and practical exercises to the finalists of the Banggai Regency education ambassadors. The results of this activity, participants were able to apply basic public communication techniques that are contained in communication on stage and psychological communication as Education Ambassadors of Banggai Regency Election event so that they are expected to become inspirational education ambassadors.